Buried in the Red Dirt Race, Reproduction, and Death in Modern Palestine - Hasso, Frances S. (Social Sciences, 2021)
Bringing together a rich and vivid array of analog and non-traditional sources, including colonial archives, newspaper reports, literature, and interviews, this book tells a story of life, death, and reproduction, during and since the British colonial period in Palestine. Available Open Access on Cambridge Core.?